Controllable Synthesis of All Inorganic Lead Halide Perovskite Nanocrystals with Various Appearances in Multiligand Reaction System - Chen, Chen (Nanomaterials (Basel), 2019)
All inorganic cesium lead halide (CsPbX(3), X = Cl, Br, I) perovskite nanocrystals (PNCs) exhibit promising applications in light-emitting devices due to their excellent photophysical properties. Herein, we developed a low-cost and convenient method for the preparation of CsPbX(3) PNCs in a multiligand-assisted reaction system where peanut oil is applied as a ligand source. The mixed-halide PNCs with tunable optical-band gap were prepared by mixing the single-halide perovskite solutions at room temperature. The resulting PNCs had good monodispersity, with dimensions of 8–10 nm, high photoluminescence quantum yield (96.9%), narrow emission widths (15–34 nm), and tunable emission wavelength (408–694 nm), covering the entire visible spectrum. Additionally, various morphologies of PNCs, such as nanospheres, nanocubes, and nanowires, were obtained by controlling reaction temperature and time, and the amount of oleamine with multiple ligands in peanut oil potentially playing a dominant role in the nucleation/growth processes of our PNCs. Finally, the resulting CsPbBr(3) PNCs were employed to develop a white light-emitting diode (WLED), demonstrating the potential lighting applications for our method.